Boardroom Dynamics: Exploring the Intersection of Corporate Governance and Firm Performance - Sushil Kumar Pradhan, Ashok Kumar Sar (Journal of Informatics Education and Research, 2024)
The requirement for strong corporate governance in the modern economy is becoming more widely acknowledged in the framework of accounting for growth. Although corporate governance is seen as the pinnacle in today's economies, it is crucial for a company's entire development and progress. The ancient economies of India and Greece are where corporate governance first emerged. The study on the relationship between corporate governance and firm performance is examined in-depth in this article. The information were taken from Scopus's online databases. The performance of the firm has been shown to benefit from good corporate governance, and this has a favorable impact on national economic growth This article highlights the key conclusions and offers suggestions for further research into the relationship between effective corporate governance and firm performance. The study also presents intriguing conclusions about the relationships between corporate governance and performance of firms, and it also offers potential directions.